2003
DOI: 10.1179/026708303225008257
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and its influence on refining performance of AlTiC master alloys

Abstract: The microstructures of four different AlTiC master alloys produced through a new method involving the reaction of pure Ti and carbon in an Al melt have been examined using XRD, SEM, EPMA, and TEM, and their re ning ef ciencies tested. Individual TiC particles were found to be single crystals with polyhedral or spherical morphologies. In addition to the aluminium matrix, Al -5Ti -0 . 3C (wt-%) re ners contain TiC and TiAl 3 phases, whereas Al -8 . 4Ti -1 . 8C contains only TiC. Three types of agglomerating beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…7). We have concluded that Al-Ti-C and Al-Ti-B master alloys share some common rules in refining Al [7], which can be further confirmed in the present work. In the Al melt with the addition of Al-Ti-B or Al-Ti-C mastera alloys, surplus Ti atoms as solute have been observed to segregate to TiB 2 or TiC particles [11][12][13]7].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…7). We have concluded that Al-Ti-C and Al-Ti-B master alloys share some common rules in refining Al [7], which can be further confirmed in the present work. In the Al melt with the addition of Al-Ti-B or Al-Ti-C mastera alloys, surplus Ti atoms as solute have been observed to segregate to TiB 2 or TiC particles [11][12][13]7].…”
Section: Resultssupporting
confidence: 87%
“…We have concluded that Al-Ti-C and Al-Ti-B master alloys share some common rules in refining Al [7], which can be further confirmed in the present work. In the Al melt with the addition of Al-Ti-B or Al-Ti-C mastera alloys, surplus Ti atoms as solute have been observed to segregate to TiB 2 or TiC particles [11][12][13]7]. It is possible that an especially thin layer of TiAl 3 phase forms at surfaces of TiB 2 or TiC particles due to the segregation of Ti, then this phase acts as substrates for the nucleation of α-Al [12][13].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Comparing to Al-Ti-B grain refi ner, the TiC, a heterogeneous nucleation core, has less conglomeration tendency than TiB 2 and is immunizing to Zr, Cr, Mn, and V [2] . Al-Ti-C is studied emphatically and is a novel kind of grain refi ner with better application prospect [3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%